The Realization of Brown - Levinsonâ€™s Politeness Strategies in the Movie â€œThe Proposalâ€ - Azmi, Mia Nurul; Hartono, Rudi (English Education Journal, 2021)
Communication is a main part in a society. In every society, there are some styles and ways of using language. There are two kinds of communication, verbal and non-verbal communication. Non-verbal communication can be gesture or expression. The purpose of this study was to analyze the positive and negative politeness strategies used by the speakers in the conversations of The Proposal movie. Method of data analysis were done by using Brown and Levinson’s Politeness Theory. The results of this study show some findings. There were positive politeness strategies used in the utterances with the highest data was performed by the the seek agreement sub-strategy - 18,6%; and the lowest was performed by assert or presuppose speaker’s knowledge of and concern for hearer’s wants sub-strategy - 1,2%. In the negative politeness strategy, the highest data was performed by the impersonalize speaker and hearer sub-strategy – 39,3%%; and the lowest was performed by apologize sub-strategy – 1,4%. It can be concluded from the study, the difference between positive and negative strategies is the relationship between the speaker and listener, and the language used in speech.